(untitled) (Research, Society and Development, 2021)
Providing healthcare to foster minors is challenging, given the family and institutional risk factors. This scoping review aimed to identify characteristics of articles on these minors’ health, published in PubMed from 2010 to 2020, following the Joanna Briggs model. The research question was developed with the PCC acronym. Half of the 252 articles were from the United States; most were from the Health Sciences, then multidisciplinary ones, and from the Human Sciences. Under Health, Medicine published the most, then Dentistry, Public Health, Nursing, Nutrition, and Pharmacy. Psychology represented the Human Sciences. In Medicine, there were studies from Pediatrics, Psychiatry, Endocrinology, and Parasitology. The participation of Pediatrics, Psychology/Psychiatry, and Dentistry increased over time. The types of care (of which, foster care and child welfare system were the most prevalent) associated with continents, reflecting a deinstitutionalization in America, Europe, and Oceania. The most approached health topics were mental, physical, and oral health, and the need for health services. The increased number of health publications, predominantly in developed countries and addressing various problems, confirms this group’s vulnerability, evidencing the need for public policies.